(untitled) (Journal of Medical & Health Sciences Review, 2025)
The study included 200 obese anemic subjects (100 with general obesity and 100 with abdominal obesity) of age 21-60 years. Subjects’ selection was made through convenience sampling technique. The socio-demographic information was obtained by interviewing the subjects and recorded in specific questionnaire. Anthropometric measures included weight, height and waist circumference (WC). Body mass index (BMI) was calculated using the measured weight and height of subjects. Biochemical data included hemoglobin level, fasting blood glucose level and lipid profile. The clinical data included only blood pressure measurement. Hemoglobin level was used as the first screening step in selection of subjects; whereas, BMI and WC were used as second screening step. The collected data was analyzed using the statistical software SPSS and the results were presented in the form of either mean±SD or frequencies (%). Relationship of BMI and WC with the biochemical and clinical variables was determined using Pearson’s correlation. The results revealed that the overall mean age of subjects was 39.9±10.1 years. Mean hemoglobin level of all subjects was 10.6±1.3mg/dl. Most of the subjects (54%) were mildly anemic. Mean weight, height, BMI and WC of all subjects were 80.7±9.8 kg, 165.0±4.9 cm, 29.7±3.6 kg/m2 and 90.1±10.1 cm, respectively. Overall, Most of the obese anemic subjects (54%) had elevated glucose levels with an overall mean fasting blood glucose level (FBG) level of 109.4±18.9 mg/dl. The abdominally obese subjects had significantly higher mean FBG level than the generally obese subjects (p<0.05). The overall mean triglycerides (Tg), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) levels of subjects were 186.8±85.7 mg/dl, 211.9±43.8mg/dl, 47.1±11.7 mg/dl and 127.4±47.4 mg/dl, respectively. The abdominally obese subjects had significantly higher mean Tg, TC, LDL-C levels and had significantly lower HDL-C level as compared to the generally obese subjects (p<0.05). The overall mean systolic and diastolic blood pressures of subjects were 129.1±28.7 and 85.5±14.9 mm/Hg, respectively. The generally obese subjects had significantly higher mean systolic and diastolic blood pressures than the abdominally obese subjects (p<0.05). Correlation analysis indicates that, comparatively, WC had a significant positive correlation with FBG (p<0.05); Whereas, BMI had a significant positive correlation with SBP and DBP (p<0.05). The study’s findings conclude that housewives with higher waist circumferences are more prone to experience metabolic issues. Intervention strategies like nutrition education should therefore be announced to cope with the problem.